Development and optimization of cosolvent-based blended Sertraline orodispersible films - A step to personalized medicine - Dalia M N Abouhussein; Mohamed A El Nabarawi; Samia H Shalaby; Ahmed Abd El-Bary (Universidade de São Paulo, 2022)
Abstract Personalized medicine is gaining importance in pharmacotherapeutics as it allows tailoring the drug treatment to achieve the best patient response. Orodispersible film (ODF) is easy to formulate in hospitals, produces dose flexibility to suit an individual needs, particularly for patients suffer from swallowing issues or prohibited to take fluids. Sertraline Hydrochloride (SRT) was solubilized in several cosolvents, then different SRT ODFs based on five hydrophilic polymers namely; polyvinyl alcohol (PVA), hydroxylethyl cellulose (HEC), hydroxypropyl methylcellulose E5 LV (HPMC E5 LV), sodium alginate (NaAlg) and gelatin at two concentrations (2% and 4%) were developed and characterized. The outcomes were exposed to response surface analysis to obtain the desirability results to obtain the optimized formulation. Blended ODFs were developed from 4% PVA and 2% HEC in different blends and then potassium chloride (KCl) as a pore-forming agent was added to the best formulation to investigate its dissolution enhancement effect. F14 containing 4% PVA: 2% HEC 2:1 with 5% KCl showed best physicochemical properties of suitable pH (5.6), disintegration time (6 sec), good folding endurance which released 91 % SRT after 15 min. SRT ODF is an encouraging delivery system in the course of personalized medicine for the management of depression.